2022
DOI: 10.3390/molecules27072284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Tannins and Flavonoids from Traditionally Used Medicinal Plants with Biofilm Inhibitory Effects against MRGN E. coli

Abstract: In the search for alternative treatment options for infections with multi-resistant germs, traditionally used medicinal plants are currently being examined more intensively. In this study, the antimicrobial and anti-biofilm activities of 14 herbal drugs were investigated. Nine of the tested drugs were traditionally used in Europe for treatment of local infections. For comparison, another five drugs monographed in the European Pharmacopoeia were used. Additionally, the total tannin and flavonoid contents of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Considering that ethanol–water is a popular solvent for tannin extraction [ 28 ], the colorimetric tannin detection method from European Pharmacopeia was applied. It has to be taken into account that in this method, the tannin content is normalized to the redox potential of pyrogallol, suggesting that there might exist biases due to different redox potentials of the different tannins (e.g., catechines vs. gallotannins) [ 29 ]. Tannins are classified as hydrolyzable (gallic acid and ellagic acid) and condensed (proanthocyanidins) tannins [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that ethanol–water is a popular solvent for tannin extraction [ 28 ], the colorimetric tannin detection method from European Pharmacopeia was applied. It has to be taken into account that in this method, the tannin content is normalized to the redox potential of pyrogallol, suggesting that there might exist biases due to different redox potentials of the different tannins (e.g., catechines vs. gallotannins) [ 29 ]. Tannins are classified as hydrolyzable (gallic acid and ellagic acid) and condensed (proanthocyanidins) tannins [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of the extracts were carried out in accordance with the monograph 2.8.14 available in the European Pharmacopoeia. In short, according to Neumann 2022 [ 29 ], the drugs were pulverized, and approximately 500 mg was extracted with boiling water (150 mL) for 30 min. The water extract was filtered and split into two parts of equal volume.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study by Neumann et al [ 92 ], when exploring the antimicrobial activity of several plant extracts against multidrug-resistant E. coli , they found that the inhibitory activity was mostly related to the tannin concentration rather than flavonoids (especially in alcoholic extracts). This finding is consistent with the presence of tannins in both Cinnamomum sp.…”
Section: Discussionmentioning
confidence: 99%
“…This method is based on photometric analysis of a color complex, the color complex being formed by boric acid and oxalic acid. The method was described in detail in the publication by Neumann et al [ 47 ] The second method was a HPLC method which allowed quantification of four main flavonoids (hyperoside, isoquercitrin, quercetin, and 2″‐ O ‐galloylhyperoside). A Shimadzu chromatography system (LC‐20AD, Shimadzu Scientific Instruments, Nakagyo‐ku) with a photodiode array detector (PDA) was used.…”
Section: Methodsmentioning
confidence: 99%